Design and test of laser-controlled paddy field levelling-beater - Zhou, Hao; Hu, Lian; Luo, Xiwen; Tang, Lingmao; Du, Pan; Mao, Ting; Zhao, Runmao; He, Jing (International Journal of Agricultural and Biological Engineering, 2020)
The technology for implementing a precise soil beating after precise soil levelling was proposed to improve the flatness of the paddy field and shorten the cycle time between the soil beating and levelling; in addition, a laser-controlled paddy field levelling-beater was designed according to the working principle. And the grade and tilt of the levelling scraper and beating mechanism are automatically controlled according to the levelling-beater vertical height and the tractor roll angle, respectively. The designed levelling-beater is capable of precise levelling and beating paddy fields at the same time with an adjustable beating depth. A paddy field test of the levelling-beater was conducted to compare the performance under both manual and automatic control modes, with the roll angles of the tractor and the levelling-beater measured using two attitude and heading reference systems (AHRSs), and the change in grade of the levelling-beater was measured using a global navigation satellite system (GNSS). The test results demonstrate that the operational quality of the levelling-beater is more stable when operating in automatic control mode than when operating in manual control mode. More specifically, the elevation of the levelling-beater varied ±4 cm around the mean elevation and roll angle varied within the range of ±0.5° when operating in automatic control mode. However, when operating in manual control mode, the elevation and roll angle were greater than ±11 cm and ±2.5°, respectively. The test results also demonstrate that the laser-controlled paddy field levelling-beater significantly improves the paddy field flatness, and enables it to operate at a stable depth to realise an even levelling and beating layer. More specifically, the maximum variation of elevation was reduced from 26.4 cm before the levelling and beating operation to 11.5 cm after the operation. In addition, the standard deviation of the elevation was reduced from 4.13 cm to 2.18 cm after the operation. The total number of flatness sampling points with the absolute difference of the desired elevation less than or equal to 3cm was more than 86%. The effective beating depth was 14.2 cm, compared with the set beating depth of 15cm, and the standard deviation of the beating depth was 2.46 cm. Keywords: laser control, levelling, beating, paddy field, flatness DOI: 10.25165/j.ijabe.20201301.4989 Citation: Zhou H, Hu L, Luo X W, Tang L M, Du P, Mao T, et al. Design and test of laser-controlled paddy field levelling-beater. Int J Agric & Biol Eng, 2020; 13(1): 57–65.